The Waste Separation Game to Promote Computational Thinking Through Mixed Reality Technology - Phatarametravorakul, Worapat; Cheevanantaporn, Suphitsara; Jamsri, Pornsuree (My University, 2022)
The primary issue of garbage is its direct impact on the environment and quality of life. Several types of trash have piled up in Thailand. Many individuals don't use the correct way of waste management because they have lacked knowledge and understanding of how to sort rubbish since childhood. To increase the possibility to fully utilize the knowledge of waste separation correctly, the researcher aims to promote computational thinking through the learning of a game called 'Trashman'. This game simulates various objects for situations of sorting garbage into the appropriate sorting bin. Trashman has 3 levels in the game. Each level increases the number of bins and the amount of garbage, starting from level 1-3 which refers to easy, moderate, and difficult levels, respectively. The level indicates the error of separating the waste if putting it into a wrong bin type. The educating about different types of waste separation through the game utilizes Mixed Reality (MR) technology of the Magic Leap One device. The developer's expectation for an alternative learning medium in the form of a game is to allow players to apply their knowledge by practicing computational skills by sorting garbage correctly. The game evaluates and summarizes scores of each level at the game's end. This will evaluate player's performance of CT through their ability separating trash. Moreover, the Sustainable Development Goals can be applied for lifelong learning to follow-up and assessment in furtherance of correct trash sorting.
Keywords: Computational Thinking; Environment; Mixed Reality Technology; Waste Separation